The initial stages of formation of low angle boundaries within lamellar bands during accumulative roll bonding of aluminum - Quadir, Md Zakaria; Ferry, M.; Munroe, P. (Elsevier, 2011)
The nature of newly forming lamellar band boundaries was investigated in accumulative roll bonded aluminum. These boundaries initiate as low angle interfaces parallel to the existing lamellar band boundaries irrespective of the crystallographic orientation of the parent lamellar band. The transverse directions of the divided segments were found to rotate at an angle equal to the degree of misorientation between segments. Such a phenomenon is not sustained when the boundaries become high angle.